Analysis of Opportunities and Threats of Trade in Plantation Products: A Case Study on Palm Oil and Coffee Trade between Indonesia and Malaysia - Silvi Siti Fauziah; Daspar Daspar (Review of International Economic, Taxation, and Regulations, 2025)
This study analyzes the opportunities and challenges of trade with Indonesian plantation products with Malaysia. Key ingredients such as palm oil and coffee are focused on considering that Malaysia is one of Indonesia's most important trading partners and a competitor in the plantation industry. The purpose is to identify potential for trade expansion, sectoral development, and policy improvement in both plantation industries.A qualitative comparative approach is employed, supported by literature analysis from official sources such as the Central Bureau of Statistics (BPS). Export structures, production volumes, and product diversification are analyzed to assess Indonesia’s competitive advantages. Findings show that Indonesia and Malaysia have similar plantation export profiles, with Indonesia benefiting from higher volume and diversification. However, global price fluctuations, sustainability demands, and Malaysia’s strict quality standards pose significant challenges. The study concludes that Indonesia holds promising opportunities to enhance its trade performance through improved production efficiency, sustainable practices, and strategic bilateral cooperation in both sectors.